Hip Morphology in MPS-1H Patients: An MRI-based Study. Issue 9 (October 2018) - Breyer, Sandra R.; Muschol, Nicole; Schmidt, Mona; Rupprecht, Martin; Babin, Kornelia; Herrmann, Jochen; Stücker, Ralf
Abstract : Background: Hip dysplasia is common in mucopolysaccharidosis type-1H (MPS-1H) patients, but its morphology is not completely understood. No magnetic resonance imaging (MRI)-based studies have been reported in the literature. The purpose of this study was to improve knowledge of hip dysplasia pathology by describing the hip morphology of these patients in MRI scans, plain radiographs, and arthrograms. Methods: We performed a retrospective chart review of 18 MPS-1H patients. Supine anteroposterior pelvic radiographs of 36 hips and MRI scans of 18 hips were analyzed. Six arthrographs were also available. Results: Plain radiographs were available for 18 patients. The mean age was 6.0 (SD=3.8) years. The mean acetabular index (AI) was 36.2 degrees (SD=5.8), and the mean migration percentage was 59.0% (SD=17.2). MRI data were available for 9 patients. The MRI findings were compared with the radiographs of the same patient. The mean AI (39.3 degrees, SD=5.8) was confirmed by the MRI findings (39.1 degrees, SD=5.5). The migration percentage was lower in the MRI scans than in the radiographs. Radiologically, the center-edge angle was negative in all patients, with a mean of −16.8 degrees (SD=7.9), and the MRI images produced a more negative value (−19.6 degrees, SD=7.6). The soft tissue coverage of the femoral head was described with the inclusion of the cartilaginous roof and labrum. The cartilaginous AI was 22.4 degrees (SD=7.5), and the labral AI was 13.5 degrees (SD=6.7). All 6 arthrograms revealed stability during dynamic testing. Conclusions: This study provides the first description of hip morphology in MPS-1H patients through MRI-based data. The cartilaginous coverage of the hip was increased compared with that of healthy children. The use of radiography alone may lead to a misunderstanding of hip morphology. MRI and arthrogram is highly recommended if surgery is considered.